Fast Assessment of Resistance to Carbapenems and Ciprofloxacin of Clinical Strains of Acinetobacter baumannii - Bou, Germán (American Society for Microbiology, 2012)
Infections caused by multidrug-resistant Acinetobacter baumannii constitute a major life-threatening problem worldwide, and early adequate antibiotic therapy is decisive for success. For these reasons, rapid detection of antibiotic susceptibility in this pathogen is a clinical challenge. Two variants of the Micromax kit were evaluated for a rapid detection in situ of susceptibility or resistance to meropenem or ciprofloxacin, separately, in 322 clinical isolates. Release of the nucleoid is the criterion of susceptibility to the beta-lactams (carbapenems), whereas diffusion of DNA fragments emerging from the nucleoid characterizes the quinolone activity. All the susceptible and resistant strains were correctly categorized in 100 min according to the MIC results and CLSI criteria. Thus, our technology is a promising tool for rapid identification of carbapenem and quinolone resistance of A. baumannii strains in hospital settings.